BODY IMAGE PERCEPTION AND NUTRITIONAL FULFILLMENT BEHAVIOR IN ADOLESCENTS - Wigunantiningsih, Ana; Remedina, Gipfel; Sari, Reni Puspita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Adolescents experience many problems related to health and nutrition due to various physical, psychological and psychosocial change, including accelerated growth and development of the body, lifestyle changes and poor eating behavior. The purpose of this study was to determine the perception of body image and nutritional fulfillment in adolescent girls. This study is an analytical observational study with a cross sectional approach. This research was conducted at MAN 1 Karanganyar in July-August 2023. The sample in this study was class XII adolescent girls totaling 42 respondents, taken by simple random sampling technique. The research instrument uses questionnaires. Data analysis was carried out univariate and bivariate. The results of the study obtained the majority of respondents had a perception of body image with a moderate category as many as 26 respondents (59.1%), respondents who had adequate nutritional fulfillment habits amounted to 21 people (47.7%). There is a significant correlation between the perception of adolescent girls' body image with nutritional fulfillment behavior with p value 0.21 0.05. There is a significant positive correlation between the perception of adolescent girls' body image and behavior with a correlation coefficient value of 0.322, meaning that the relationship between the two variables is sufficient.